VIOLENCE AGAINST WOMEN IN TURKEY AND THE RESPONSIBILITY OF PUBLIC ADMINISTRATION - Polat TUNÇER (International Journal of Eurasia Social Sciences, 2017)
The violence seen by women in our country has increased in recent years. This situation has social, economic, psychological, cultural and legal aspects. In order to solve this social problem, the public administration must take the necessary precautions first. The public administration must take legal, economic, social and cultural precautions in particular. Violence is widespread in societies that are uneducated, deprived and poor, deprived of value judgment, and subjected to cultural degeneration. In addition, many social problems also arise in such a society, and such problems also support and spread violence. This leads to many problems that the public administration needs to solve. For this reason, the public administration should take measures to prevent violence from spreading and spread.In our day and in our country, women are still being subjected to psychological and physical violence and are even killed. Statistics of women killed by their spouses or lovers by public administration are published. On the other hand, it is very difficult to determine the number of women who are exposed to abuse and abuse. However, events reflected in the courts and recorded in police records can be detected. Unfortunately, most of our women who have experienced domestic violence have no information or security to search for their rights. And he has to take the violence he sees to the theater. The spread of violence in the family means the spread of problematic children. This is a question that should be solved by the public administration in every way. It is possible to change and transform society through education, but only through the social policies of the public administration. For this reason, the responsibility of public administration is great in reducing or eliminating violence against women. Public administration has to take legal, social, economic and cultural precautions. The Ministry of Family and Social Policy was established on this subject. Unfortunately, as we look at the situation in our country, it is difficult to say that an adequate and satisfactory work has been done. However, in the prevention of violence against women, all collective responsibility and obligations as well as public administration fall. It is inevitable that everybody else plays an active role in this matter. For the protection and respect of women who raise future generations is a conscientious and human necessity.